Problem-Based Learning To Improve Concept Understanding and Critical Thinking Ability of Science Education Undergraduate Students - Mellyta Uliyandari; Emilia Candrawati; Anna Ayu Herawati; Nurlia Latipah (IJORER : International Journal of Recent Educational Research, 2021)
This reserach was conducted to improve conceptual understanding and critical thinking ability of fourth-semester students of the Science education study program, Bengkulu University by applying PBL. The research method used in this study is quasi experimental, which in its implementation uses single class or one group pretest-posttest design. The test question was the instrument used in this study. The findings showed that there was an improvement in students‘ conceptual understanding and critical thinking ability of students‘ since implementing problem-based learning models in environmental chemistry courses. This improvement can be seen from the results of the gain test for each class group on the test of conceptual understanding and critical thinking ability which are in the "medium" category, while the t-test results for concept understanding and critical thinking ability show a significant difference (0.000 <0.05). ), In other words, the implementation of the PBL learning influences the students‘ conceptual understanding and critical thinking ability. Further the implementation of the problem-based learning model in teaching and learning process presents problems with real conditions so that it can stimulate students to not only think and understand at the rote level but also interpret the problem. Quiet in-depth research on the implementation of problem-based learning models in learning is highly recommended to get more comprehensive results.